Fr. José Maurício: the individuality of his prosodic solutions (Per Musi, 2019)
We started with the systematic relation between prosodic accents and dissonant chords, discovered in a small choral music work of Fr. José Maurício Nunes Garcia, composed at his initial phase. We looked for this procedure on his choral works of the period, comparing them with other composers’ works of the same time who were working in Brazil. Finally, we tried to find the continuity of his interest for prosody, in two of his most important works, composed in later moments.